Fabrication and Characterization of the self support enriched 107, 109Ag thin targets for heavy ion induced transfer reaction. (1st February 2022) - Vinayak, A.; Abhilash, S.R.; Hosamani, M.M.; Hiremath, G.B.; Umapathy, G.R.; Khandelwal, D.; Madhavan, N.; Kabiraj, D.; Badiger, N.M.
Abstract: The enriched, self-supported, and thin isotopic targets of 107 Ag and 109 Ag were fabricated at the target development laboratory, IUAC New-Delhi, using a vacuum deposition facility. The targets were fabricated by the thermal evaporation technique with minimum material consumption. The simple and efficient method for the fabrication of thin targets with high quality without major impurities was discussed in detail. The prepared targets were characterised by using Rutherford Backscattering Spectrometry, X-Ray Diffraction, Total-Reflection X-Ray-Fluorescence and Scanning-Electron-Microscope techniques. From the characterizations, it was found that the fabricated targets were quite stable, had the same crystalline nature, the absence of any other elements, and were suitable for nuclear reaction experiments.